2010
DOI: 10.2298/avb1001031a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the sterol demethylation-inhibiting fungicide fenarimol on selected biochemical parameters in rats

Abstract: Fenarimol, a 2,4'-dichloro-α-(pyrimidin-5-yl) benzhydryl alcohol fungicide and steroid demethylation inhibitor, has been reported to affect the actions of multiple CYP450 isoforms, including key enzymes. The aim of this study was to evaluate the effects of fenarimol on a set of biochemical parameters in rats. Rats were intraperitoneally injected with a 200 mg kg-1 dose of fenarimol. Blood samples were collected for measurements of serum alkaline phosphatase (ALP), alanine amino transferase (ALT), aspartate ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Again, as a result of studies in experimental animals, fenarimol has been shown to have teratogenic and oncogenic effects on reproduction and inhibit aromatase activity in male rats [20]. In addition, as a result of a previous study conducted by our group, it was shown that hepatic marker enzyme activities (ALP, ALT, AST and CK) and some biochemical parameters in serum were affected in fenarimol-induced rats [21].…”
Section: Introductionmentioning
confidence: 87%
“…Again, as a result of studies in experimental animals, fenarimol has been shown to have teratogenic and oncogenic effects on reproduction and inhibit aromatase activity in male rats [20]. In addition, as a result of a previous study conducted by our group, it was shown that hepatic marker enzyme activities (ALP, ALT, AST and CK) and some biochemical parameters in serum were affected in fenarimol-induced rats [21].…”
Section: Introductionmentioning
confidence: 87%